Review on Spirulina ( Green Alage) - Bhushan G. Rajput; Bhushan S. Kanade; Bhagyashri Ishi; Bhagyashri Dhangar; Paresh A. Patil (International Journal of Pathogens, 2024)
Spirulina is an edible blue-green algae that is a plant protein source. In recent years, its health benefits have attracted scientific attention, including micro-level examinations of the algae's bioactive components. As proof of concept, investigations conducted in vitro, in vivo, and ex vivo have shown how spirulina works and how it affects immunity. Spirulina has been used as a whole food and as a nutritional supplement for many years. It has been shown to have positive effects on a variety of human health problems, such as malnutrition, metabolic syndrome, and more.The bioactives in Spirulina, including essential amino acids, Phycocyanins, Polysaccharides, Carotenoids, Chlorophylls, Vitamins, and trace Minerals, play a holistic role in its anti-oxidative, anti-inflammatory, antibacterial, immune-modulating, and anti-malignancy actions. Phenolic compounds, extracellular metabolites, and Spirulina whole food has been shown to have anti-bacterial effects on the epithelial lining of the gut. This is thought to be due to the phenolic compounds, extracellular metabolites, and antibacterial properties of Spirulina that are released after digestion. The prebiotic effect of Spirulina on the gut microbiota is thought to be increased due to the fiber content.In this study, Spirulina was determined to be digestible by measuring free amino acid and peptide release at each stage of digestion in a model of a static digestive system.The hypothesis that poor gut health can lead to low level inflammation and metabolic syndrome and that nutritional supplementation such as Spirulina can help address these issues in the long term can be beneficial in reducing comorbid illnesses associated with the current coronavirus disease pandemic.
Keywords: Algal proteins; Amino acids; Arthrospira platensis; Bioactive; Immune system; antioxidants; chronic disease; digestion; gut health; metabolic syndrome; microbiome; peptides; spirulin